Phenolic profiling of Silybum marianum (L.) Gaertn (milk thistle) by HPLC-DAD-ESI/MS - Pereira, Carla (2015)
Milk thistle (Silybum marianum (L.) Gaertn., Asteraceae) is an annual to biennial herbaceous plant native to the Mediterranean basin. The main pharmacologically active constituents of mik thistle fruits are flavonoligans such as silybin A, silybin B, isosylibin A, isosylibin B. silychristin, isosilychristin, and silydianin [2]. and they possess antioxidant and hepatoprotective properties [1]. The aim of this study was to compare the phenolic profiles of milk thistle infusion and hydromethanolic extract with the aid of HPLC-DADESIIMS. Similar phenolic profiles were observed for the two preparations, with only quantitative differences between them. The infusion revealed a higher concentration in total phenolic compounds (5.57 mg/g) than the hydromethanolic extract (3.56 mg/g), with apigenin-7-O-glucuronide as the major compound in both preparations (3.14 mg/g in the infusion, and 0.58 mg/g in the hydromethanolic extract). Total flavonoids were higher in the infusion (4.66 mg/g), with apigenin-7-O-glucuronide, luteolin-7-O-glucuronide (1.17 mg/g), and apigenin-O-deoxyhexosyl-glucuronide (0.36 mg/g) as the main constituents. The hydromethanolic extract showed a higher content of total phenolic acids (1.65 mg/g), including 5-O-caffeolyquinic and protocatechuic acids (0.56 and 0.44 mg/g, respectively). Besides these phenolic acids, the hydromethanolic extract also revealed high levels of luteolin-7-O-glucuronide (0.58 mg/g).